2021
DOI: 10.21203/rs.3.rs-136815/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stroboscopic operando spectroscopy of the dynamics in heterogeneous catalysis by event-averaging

Abstract: Heterogeneous catalyst surfaces are highly dynamic entities that respond rapidly to changes in their local gas environment, and the dynamics of the response is a decisive factor for the catalysts’ action and activity. Few probes are able to map catalyst structure and local gas environment simultaneously under reaction conditions at the time scales of the dynamic changes. Here we use the CO oxidation reaction over a Pd(100) surface exposed to pressures of 3 and 100 mbar of a CO + O2 gas mixture to demonstrate h… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…65 In the last decade, the potential of NAP-XPS to contribute to the understanding of commercially important thin lm growth processes has been realised, and although there remain rather few published studies, investments are being made to support these challenging experiments at a number of synchrotron sources, including at the SPECIES and HIPPIE beamlines at MAX-IV. 66,67 The pressure used in atomic layer deposition (ALD) (and the useful range in some chemical vapour deposition (CVD) processes) is typically in the 10 À3 to 20 mbar range, which is well-matched to NAP-XPS. 23 However, there are also formidable challenges.…”
Section: Thin Lm Growthmentioning
confidence: 99%
“…65 In the last decade, the potential of NAP-XPS to contribute to the understanding of commercially important thin lm growth processes has been realised, and although there remain rather few published studies, investments are being made to support these challenging experiments at a number of synchrotron sources, including at the SPECIES and HIPPIE beamlines at MAX-IV. 66,67 The pressure used in atomic layer deposition (ALD) (and the useful range in some chemical vapour deposition (CVD) processes) is typically in the 10 À3 to 20 mbar range, which is well-matched to NAP-XPS. 23 However, there are also formidable challenges.…”
Section: Thin Lm Growthmentioning
confidence: 99%
“…Using internal reference signals found by image recognition, Knudsen et al 4 demonstrated event averaging over many ambient-pressure X-ray photoelectron spectroscopy (APXPS) pulse/probe cycles such that time-resolved X-ray photoelectron (XP) spectra with otherwise poor statistics could be improved to obtain a sufficient signal-to-noise ratio, without losing time resolution. By searching for a lock-in signal in the data itself, the method allows for averaging data originating from nonstrictly periodic reactions or experiments with significant time deviations from supposedly periodic events (e.g., valve opening, gas flow, or spectra collection).…”
Section: T H Imentioning
confidence: 99%
“…14 On the other hand, as it was demonstrated in the previous literature, tr-APXPS experiments become complicated by the additional drop in the count rate because of the scattering of electrons by the gas phase at elevated pressures. 4,15,16,30 Additional challenge for tr-APXPS with rapid pressure/chemical perturbations is needed to generate gas pulses with time constants that are comparable to those of the time resolution of the experiment. Such gas pulse perturbations can be achieved through gas flow control by mass flow controllers (MFCs) 15 or using supersonic molecular beams (SSMBs).…”
Section: T H Imentioning
confidence: 99%
See 1 more Smart Citation
“…49 Time resolved APXPS experiments have also been developed 50,51 and experiments with time resolution of 50 ms have very recently been reported. 52 AP-XPS instruments also provide means to measure the gas composition in front of the surface, with XPS, and in the bulk gas mixture, with mass spectrometer(s), which allows the surface composition to be linked to the reactivity. Care must be taken in using mass spectrometry (MS) as comparison of NAP-XPS, Planar Laser Induced Floresence (PLIF) and MS shows that the composition directly in front of the surface is different to the average composition in the reactor, which is what is sampled by MS in most cases.…”
Section: Introductionmentioning
confidence: 99%